Manajemen Keuangan Keluarga di Era Pandemi Covid -19 - Efrita Norman; Enah Pahlawati; Rio Kartika Supriyatna (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
In 2020, the world community was shocked by the spread of Corona Virus Disease (Covid-19) in various countries, so far based on WHO data, 233 countries have cases of Covid-19, including Indonesia. As an anticipatory measure for the Indonesian government in cutting the chain of the spread of the corona virus, the Indonesian government issued government regulation Number 21 of 2020 concerning Large-Scale Social Restrictions (PSBB), the increasing number of the spread of the corona virus in Indonesia, the government issued a new policy on July 31, 2021 regarding PPKM where The movement of people is restricted to reduce the spread of the corona virus. This has an impact on people's economic conditions that are not easy, the unemployment rate is so complex. This research is a qualitative research using the literature study method where the author collects data, studies, and analyzes from the literature published by books, journals, and magazine articles so as to obtain accurate and in-depth data about family financial management. The results of this study are financial management. family is very important because we do not live alone but we are part of the family, society and the country as for the steps we take in managing family finances are as follows: (1) record expenses that must be spent monthly, (2) record all expenses that may or may not be monthly, (3) record all monthly passive income (4) record all monthly active income (5) add up monthly expenses plus expenses may or may not monthly (6) add up monthly passive income with active income per month.(7) calculate the difference in the sum n point 5 with point 6 (8) targeting our financial condition by multiplying monthly expenses by 12. one month. And the key to success in managing family finances is to increase self-capacity, want to learn more, and want to fight again and be able to refrain from being consumptive.In 2020, the world community was shocked by the spread of Corona Virus Disease (Covid-19) in various countries, so far based on WHO data, 233 countries have cases of Covid-19, including Indonesia. As an anticipatory measure for the Indonesian government in cutting the chain of the spread of the corona virus, the Indonesian government issued government regulation Number 21 of 2020 concerning Large-Scale Social Restrictions (PSBB), the increasing number of the spread of the corona virus in Indonesia, the government issued a new policy on July 31, 2021 regarding PPKM where The movement of people is restricted to reduce the spread of the corona virus. This has an impact on people's economic conditions that are not easy, the unemployment rate is so complex. This research is a qualitative research using the literature study method where the author collects data, studies, and analyzes from the literature published by books, journals, and magazine articles so as to obtain accurate and in-depth data about family financial management. The results of this study are financial management. family is very important because we do not live alone but we are part of the family, society and the country as for the steps we take in managing family finances are as follows: (1) record expenses that must be spent monthly, (2) record all expenses that may or may not be monthly, (3) record all monthly passive income (4) record all monthly active income (5) add up monthly expenses plus expenses may or may not monthly (6) add up monthly passive income with active income per month.(7) calculate the difference in the sum n point 5 with point 6 (8) targeting our financial condition by multiplying monthly expenses by 12. one month. And the key to success in managing family finances is to increase self-capacity, want to learn more, and want to fight again and be able to refrain from being consumptive.